S100B serum protein cannot predict secondary intracranial haemorrhage after mild head injury in patients with low-dose acetylsalicylic acid prophylaxis. (2nd January 2016) - Ernstbrunner, Lukas; Korn, Gundobert; Ernstbrunner, Erich; Auffarth, Alexander; Tauber, Mark; Resch, Herbert; Moroder, Philipp
Abstract: Introduction : The goal of this study was to investigate if S100B serum protein could predict secondary intracranial haemorrhagic events (SIHEs) after mild head injury (mHI) in patients taking low-dose acetylsalicylic acid (LDA), making routinely repeated head computed tomography (RRHCT) scans unnecessary. Methods : Three hundred and eight-two patients with mHI, older than 60 years and taking LDA prophylaxis were enrolled. Primary head CT and RRHCT scans within 3 and 48 hours to trauma were performed. Additionally, S100B serum protein levels were evaluated at admission and predictive power for SIHEs was analysed. Results : Fifty-nine per cent were female and the mean age of all included patients was 81.8 ± 8.9 years. In four patients SIHEs were diagnosed. Sensitivity and the negative predictive value of S100B serum protein (cut-off value 0.10 µg l −1 ) were 75.0% and 98.6%, respectively. Specificity was 19.0% and the positive predictive value 1.0% (306 false positive values). In patients without bleeding, the median S100B value was 0.18 (IQR = 0.12–0.34) and in the ones with SIHEs, the median was 0.11 (IQR = 0.10–1.16) ( p > 0.05). The discriminatory power of S100B in the ROC analysis was 0.399 (95% CI = 0.079–0.720; p > 0.05). Conclusion : S100B cannot be considered as an effective diagnostic tool in the prediction or exclusion of SIHE in older patients with mHIs taking LDA prophylaxis.